2002
DOI: 10.1002/eat.10084
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine in the treatment of anorexia nervosa: An open label trial

Abstract: These findings are promising with clinically significant weight gain in an outpatient setting during a brief 10-week period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 15 publications
(6 reference statements)
1
60
1
2
Order By: Relevance
“…Some findings in this study are similar to those reported in an earlier study with olanzapine 15 although the mean weight gain with quetiapine was less. However, in both studies there were significant declines in total PANSS scores and among the groups that gained weight, compared to the groups that did not gain weight, and there were improvements in certain scales of the PANSS that measure symptoms of psychosis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some findings in this study are similar to those reported in an earlier study with olanzapine 15 although the mean weight gain with quetiapine was less. However, in both studies there were significant declines in total PANSS scores and among the groups that gained weight, compared to the groups that did not gain weight, and there were improvements in certain scales of the PANSS that measure symptoms of psychosis.…”
Section: Resultssupporting
confidence: 91%
“…[12][13][14] In a study reported by our group 15 we found that a modest weight gain was accompanied by statistically significant decreases in total scores on the Positive and Negative Syndrome Scale (PANSS) which is a wellvalidated scale typically used to assess severity of psychotic symptoms in patients with schizophrenia. 16 The PANSS has seven scales that measure \positive" symptoms of schizophrenia (delusions, conceptual disorganization, hallucinatory behavior, excitement and grandiosity, suspiciousness and hostility); seven scales that measure \negative" symptoms (blunted affect, emotional withdrawal, poor rapport, apathetic social withdrawal, difficulty in abstract thinking, lack of spontaneity, stereotyped thinking); and six scales that measure general psychopathology.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that olanzapine increases body weight gain; reduces agitation, anxiety, and depression; increases ability or desire to eat; and decreases obsessive thoughts concerning body image (Barbarich et al 2004;Boachie et al 2003;Malina et al 2003;Mehler et al 2001;Powers et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine treatment in humans causes limited extrapyramidal effects and has been associated with body weight gain (Allison and Casey 2001). A few (uncontrolled) studies already reported beneficial effects of olanzapine treatment on food intake and anxiety levels of AN patients (Barbarich et al 2004;Boachie et al 2003;Malina et al 2003;Mehler et al 2001;Powers et al 2002), but no study has reported effects of olanzapine treatment on physical activity levels.…”
mentioning
confidence: 99%
“…question of whether antipsychotic medication may have a role in the treatment of AN. Olanzapine has been described in several case reports [5][6][7] and one open trial 8 as being associated with effective and sustained weight gain and some psychological improvement in AN patients. A controlled clinical trial is the necessary next step in determining whether these novel medications may, indeed, prove helpful to patients with AN.…”
Section: Antipsychoticsmentioning
confidence: 99%